Economic impact of STEM immigrant workers - Christopher F. Baum; Hans Lööf; Andreas Stephan (Global Labor Organization (GLO), 2018)
STEM-focused industries are critical to the innovation-driven economy. As many firms are running short of STEM workers, international immigrants are increasingly recognized as a potential for high-tech job recruitment. This paper studies STEM occupations in Sweden 2011–2015 and tests hypotheses on new recruitment and the economic impact of foreign STEM workers. The empirical analysis shows that the probability that a new employee is a STEM immigrant increases with the share of STEM immigrants already employed, while the marginal effect on average firm wages is positively associated with the share of immigrant STEM workers. We also document heterogeneity in the results, suggesting that European migrants are more attractive for new recruitment, but non-EU migrants have the largest impact on wage determination.
Keywords: C23; J24; J61; O14; O15; 330; STEM; migration; employment; wages; correlated random effects